2016
DOI: 10.18632/oncotarget.11997
|View full text |Cite
|
Sign up to set email alerts
|

Bladder neck preservation improves time to continence after radical prostatectomy: a systematic review and meta-analysis

Abstract: Bladder neck preservation (BNP) during radical prostatectomy (RP) may improve postoperative urinary continence, although its overall effectiveness remains controversial. We systematically searched PubMed, Ovid Medline, Embase, CBM and the Cochrane Library to identify studies published before February 2016 that assessed associations between BNP and post-RP urinary continence. Thirteen trials (1130 cases and 1154 controls) assessing BNP versus noBNP (or with bladder neck reconstruction, BNR) were considered suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 56 publications
5
36
2
2
Order By: Relevance
“…A previous systematic review and meta-analysis of 13 studies assessing bladder neck sparing (BNS) versus non-BNS techniques reported improved early and long-term recovery of urinary continence without negatively affecting oncological control. Their results were yet non-conclusive given the limitations of the studies included, and the authors suggest the need for further large, prospective, multicentre, long-term follow-up studies and RTCs to confirm them [ 25 ]. Here, we perform a critical review of the available data localising positive surgical margins after bladder neck sparing radical prostatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…A previous systematic review and meta-analysis of 13 studies assessing bladder neck sparing (BNS) versus non-BNS techniques reported improved early and long-term recovery of urinary continence without negatively affecting oncological control. Their results were yet non-conclusive given the limitations of the studies included, and the authors suggest the need for further large, prospective, multicentre, long-term follow-up studies and RTCs to confirm them [ 25 ]. Here, we perform a critical review of the available data localising positive surgical margins after bladder neck sparing radical prostatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder neck preservation improved early (6 months) continence rates and long-term (>12 months) continence rates. 33 Anastomotic leak rates, positive surgical margins, and biochemical failure rates were comparable between the two groups. More recently, Rajih et al 34 assessed 322 men who underwent robot-assisted RP in Canada, demonstrating that bladder neck preservation (hazard ratio [HR], 0.71; 95% confidence interval [CI], 0.5-0.99; P = 0.04), and prostate size (HR, 0.99; 95% CI, 0.98-0.99; P = 0.02) were independent predictors of continence recovery after surgery.…”
Section: Preservation Techniquesmentioning
confidence: 80%
“…A systematic review and meta‐analysis evaluated 13 trials, including two RCTs, six prospective, and five retrospective studies. Bladder neck preservation improved early (6 months) continence rates and long‐term (>12 months) continence rates . Anastomotic leak rates, positive surgical margins, and biochemical failure rates were comparable between the two groups.…”
Section: Peroperative Measures In the Prevention Of Uimentioning
confidence: 86%
“…Preservation of puboprostatic ligament improves the rapidity of urinary continence after radical prostatectomy . Other criteria such as a bladder neck preservation, an intussusception of the reconstructed bladder neck, or preservation of the normal urethral sphincter anatomy improve time to continence after radical prostatectomy. Thus, all of these factors may contribute to SUI after radical prostatectomy.…”
Section: Introductionmentioning
confidence: 99%